How to Be Things with Words: Speech Acts and the Ontological Symmetry Between Realism and Idealism - Souza, Euclides (Philosophy and Realistic Reflection, 2025)
This article challenges the traditional separation between language and ontology by arguing that they are fundamentally co-constitutive. Drawing from Speech Act Theory—particularly in its development by Austin, Searle, and Vanderveken—it demonstrates that language is not merely a vehicle for describing reality, but a generative force that constitutes ontological status through declarative and performative acts. Building on this framework, the paper critiques Quine’s early attempt (On What There Is, 1948) to isolate ontological commitment from linguistic practice, showing that even denial presupposes referential invocation. It further examines Word and Object (1960), where Quine acknowledges that reference and meaning are shaped by conceptual schemes, suggesting greater affinity with SAT than his earlier stance implies. Beyond the construction of institutional facts, the article defends a broader claim: that even so-called natural or physical facts are only intelligible through mental-linguistic mediation. Integrating insights from phenomenology, the philosophy of mind (Metzinger, Chalmers, Nagel), and non-Western ontologies (Buddhist pratītyasamutpāda, Ubuntu), the article demonstrates that no access to being is possible without an act of saying. Ontology does not precede language—it emerges with it. By repositioning SAT as a metaphysical framework rather than a linguistic tool, the paper proposes a model in which saying and being are inseparable operations. Language is not posterior to the world—it is what makes the world available to us as world.